The Impact of Reimbursement Practices on the Pharmaceutical Market for Off-Patent Medicines in Slovakia - Tesar, Tomas; Golias, Peter; Masarykova, Lucia; Kawalec, Paweł; Inotai, András (Frontiers in Pharmacology, 2021)
Background: The aim of this study was to investigate the impact of selected legislative initiatives and their implementation for off-patent medicinal products in Slovakia compared with the rest of the Visegrád Group (V4 countries). Methods: We analyzed the development of applications for the reimbursement of generic and biosimilar drugs. Particular emphasis was placed on (a) the availability and penetration of biosimilars from 2006 to 2020 in Slovakia, (b) a comparative analysis of biosimilars in V4 countries based on the national reimbursement lists of medicinal products for August 2021. Data relating to the sales of generic and biosimilar medicines in Czechia, Hungary, Poland, and Slovakia were based on the IQVIA MIDAS MAT July 2021. Results: The number of applications for the reimbursement of generic drugs decreased from 296 in 2016 to 165 in 2020. In financial terms, the sales of generic medicines in Slovakia increased from 21.7% in 2015 to 22.3% in 2020. Over the same period, the sales of generic drugs in Poland fell from 40.4% in 2015 to 35.0% in 2020, from 26.2% to 22.1% in Hungary, and from 29.6% to 20.4% in Czechia. When considering the 66 biosimilars registered by the European Medicines Agency (EMA), 38 drugs (58%) were available on the Slovak market as of 1st August 2021; this compared to 32 drugs (48%) in Poland, 38 drugs (58%) in Hungary, and 40 drugs (61%) in Czechia. In financial terms, the sales of biosimilars in Slovakia increased from 0.94% in 2015 to 2.00% in 2020. Over the same period, the sales of biosimilars in Poland increased from 0.59% in 2015 to 1.29% in 2020, from 0.72% to 2.23% in Hungary, and from 0.76% to 2.15% in Czechia. Conclusions: To intensify the use of generic and biosimilar medicines, we suggest the comprehensive re-evaluation of combinations of the three-threshold entry, the amount of mandatory price reductions, and external reference pricing requirements (as the average of the three lowest prices among the official prices of a medicinal product in other Member States) for generic and biosimilar drugs. We also suggest cancellation of the exception from the fixed co-payment.